The Effects of Inhaled Limnophila aromatica Essential Oil on Brain Wave Activities and Emotional States in Healthy Volunteers: a Randomized Crossover Study - Pakamon Thanatuskitti; Vorasith Siripornpanich; Winai Sayorwan; Chanida Palanuvej*; Nijsiri Ruangrungsi (Iranian Society of Pharmacognosy, 2020)
Background and objectives: Limnophila aromatica (Lam.) Merr., a characteristic odorous vegetable, is commonly used in Thai dishes and folk medicine. Limnophila aromatica essential oil has never been investigated on brain activities before. This study aimed to evaluate the effects of L. aromatica essential oil inhalation on brain wave activities through EEG recordings and emotional states among healthy volunteers using a randomized crossover design. Methods: Limnophila aromatica essential oil was extracted from the aerial parts by hydro-distillation method and its chemical components were analyzed by GC/MS. The essential oil was diluted to 8% v/v with sweet almond oil. Twenty-four healthy participants aged between 18 and 25 years, recruited from general public, inhaled both L. aromatica essential oil and sweet almond oil with seven-day washout period. Nicolet EEG v32 was used to record brain activities and the self-evaluated questionnaire on emotional states in Thai version of The Geneva Emotion and Odor Scale was used to measure the subjective feelings of the participants. Data were analyzed using paired t-test with a significance level of 0.05. Results: Limnophila aromatica essential oil icreases theta and alpha wave and induced more relaxed feelings compared to the vehicle. Conclusion: The inhalation of L. aromatica essential oil could cause the relaxing effects on positive mood states and the relaxation of brain state.